Determinant Factors of User Satisfaction in the Integrated Customs and Excise System - Lazarus Hari Sabat Prafajar; Hendy Tannady (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This research is motivated by variations in user satisfaction levels in the implementation of the Ceisa 4.0 system within Freight Forwarder companies, as well as an existing research gap concerning the influence of quality of information on perceived trust and the relationship between perceived trust and user satisfaction. The objective of this study is to analyze the influence of quality of information, perceived ease of use, perceived usefulness, and perceived trust on user satisfaction. The research employs a quantitative approach using Covariance-Based Structural Equation Modeling (CB-SEM), involving 120 respondents as user CEISA 4.0 selected through purposive sampling. The findings indicate that quality of information has a significant effect on perceived ease of use and perceived usefulness. Furthermore, perceived ease of use and perceived usefulness significantly influence user satisfaction, while the influence of quality of information on perceived trust and the influence of perceived trust on user satisfaction were found to be insignificant. Theoretically, this study contributes by confirming and extending the technology acceptance model. Practically and managerially, the results provide recommendations for system administrators to improve information quality, ease of use, and perceived usefulness in order to enhance user satisfaction and encourage continuous system utilization.